PERANCANGAN OTOMATIS TROLLEY SMARTGESTURE BERBASIS ARDUINO - Gifazil, Muhammad; Fauzi, Rahmat (Computer Science and Industrial Engineering, 2022)
Smart Gesture is one of the interesting technologies to develop. Smart gestures can be used into various things to facilitate human work. In general, trolleys are used to pack groceries that are pulled manually, with the presence of Smart Gestures trolley users do not need to spend energy to pull the trolley anymore, just control with a glove. The Smart Gesture applied to the trolley uses a gyro sensor to run the motor, so that controlling the trolley only relies on the level of hand tilt produced from the accelerometer sensor. To minimize the discharge of excess power in pulling the trolley, trolley users can control the trolley without having to pull it directly.